2007
DOI: 10.1245/s10434-007-9481-x
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Tumor M2 Pyruvate Kinase (Tumor M2-PK) as a Biomarker of Gastrointestinal Malignancy

Abstract: Tumor M2-PK is elevated in a range of gastrointestinal malignancy. In pancreatobiliary malignancy, the weight of evidence suggests that the test can be used as an adjunctive diagnostic test in conjunction with CA 19-9 and also that it may be a valuable biomarker of adverse prognosis. Stool tumor M2-PK appears to be a promising test for colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…To explore the potential functions of nuclear PKM2 in response to etoposide treatment, we fractionated the nuclear extracts of etoposide-treated and untreated MCF7 cells by size-exclusion chromatography, followed by detection of PKM2 protein. The results demonstrated that, consistent with previous findings in most cancer cells (3,(21)(22)(23), nuclear PKM2 predominantly existed in low-molecular-weight fractions (fractions 41-45) corresponding to PKM2 dimer. Unexpectedly, an aliquot part of nuclear PKM2 also existed in a high-molecular-weight (Ͼ669 kDa) fractions (fractions 24 -28) (upper panel, Fig.…”
Section: Identification Of Nuclear Pkm2-interacting Proteins In Dnadasupporting
confidence: 91%
“…To explore the potential functions of nuclear PKM2 in response to etoposide treatment, we fractionated the nuclear extracts of etoposide-treated and untreated MCF7 cells by size-exclusion chromatography, followed by detection of PKM2 protein. The results demonstrated that, consistent with previous findings in most cancer cells (3,(21)(22)(23), nuclear PKM2 predominantly existed in low-molecular-weight fractions (fractions 41-45) corresponding to PKM2 dimer. Unexpectedly, an aliquot part of nuclear PKM2 also existed in a high-molecular-weight (Ͼ669 kDa) fractions (fractions 24 -28) (upper panel, Fig.…”
Section: Identification Of Nuclear Pkm2-interacting Proteins In Dnadasupporting
confidence: 91%
“…A very high percentage of cancer patients of different cancer types have elevated levels of PKM2 in their blood circulation (22). We show that the circulative PKM2 plays a critical role in facilitating tumor growth by promoting tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 78%
“…PKM2 expression was shown to be involved in early tumorigenesis (28) and can be detected in the blood and stool of cancer patients (9,82); furthermore, increases in PKM2 levels were reported to correlate with tumor size and stage (9). As described in another article in this CCR Focus section by Yang and colleagues, mutations of IDH1 and IDH2 are also reported to be easily detectable using small amounts of tumor samples (83).…”
Section: Discussionmentioning
confidence: 96%